Wpływ inwestycji bezpośrednich oraz fuzji na zmiany w handlu międzynarodowym w latach 1990-2002 - Buszko, Andrzej (The Influence of Foreign Direct Investment And Mergering in International Trade In 1990-2002, 2005)
The aim of this article is to present the changes caused by foreign direct investment and companies mergers. The period of 1990-2002 is analyzed. The activity of International companies is examined as well. The close attention is paid to the changes of foreign trade. The trends are compared among industrial and developing countries. Some developing countries utilized the changes to participate in foreign trade cooperation, but the others are still before such a process. The main part of foreign direct investment and trade are concentrated among developed regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 28-39